2013
DOI: 10.1262/jrd.2012-021
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Age, Body Weight and Testicular Parameters in Murrah Buffalo Bulls Raised in Brazil

Abstract: Buffalo are an economically important source for meat and milk production, especially in Brazil. However, important aspects of their biology remain unknown thus far. Herein, we describe the reproductive characteristics of male Murrah buffalo (Bubalus bubalis) raised under extensive management conditions by applying biometrics associated with testicular weight. We analyzed seven males, divided into two groups: G1, which consisted of four 18-month-old animals, and G2, which consisted of three 24-month-old animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
2
10
2
Order By: Relevance
“…This is not uncommon in animals as similar observations have been made in other animal species (Derar et al 2012) where the left testis tended to be larger than the right testis in male dromedary. Other studies with similar results have been done also in Murral Buffalo bulls (Luz et al 2013) and in adult male goats (Khan et al 2014). The animal species mentioned are not same as the ones in our study but these studies show a trend that requires further investigation for this species also.…”
Section: Resultssupporting
confidence: 74%
“…This is not uncommon in animals as similar observations have been made in other animal species (Derar et al 2012) where the left testis tended to be larger than the right testis in male dromedary. Other studies with similar results have been done also in Murral Buffalo bulls (Luz et al 2013) and in adult male goats (Khan et al 2014). The animal species mentioned are not same as the ones in our study but these studies show a trend that requires further investigation for this species also.…”
Section: Resultssupporting
confidence: 74%
“…After puberty, testicular development in guinea pigs was similar to that in other mammal and rodent species (COUROT, HOCHEREAUA- DE REVIERS and ORTAVANT, 1970;ASSIS NETO, CARVALHO, MELO et al, 2003a). Highly significant correlation (p < 0.01) between body mass, age and other testicular parameters agreed with Murrah buffalo bulls (LUZ, SANTOS, ANDRIGHETTO et al, 2013) and contrasted to the correlation described only between the testis mass and the length, width and tubule diameter in collared peccary (GUIMARÃES, CARDOSO, FERREIRA et al, 2013) and between testicular mass and length and between testicular mass and width (FRANÇA, SILVA-JUNIOR, CHIARINI-GARCIA et al, 2000;FERREIRA, GUIMARÃES, LUZ-RAMOS et al, 2004;SONNER, MIGLINO, SANTOS et al, 2004;OHASHI, MIRANDA, CORDEIRO et al, 2007). Thus, highly significant correlation (p < 0.01) between age, body mass and testicular biometric data indicated that, in guinea pigs, testicular development depended both on age and body development, as in other rodent species (ASSIS NETO, CARVALHO, MELO et al, 2003a;FERREIRA, GUIMARÃES, LUZ-RAMOS et al, 2004), in opposition to other mammal species, in which testicular development rather depends on body development (COUROT, HOCHEREAUA-DE REVIERS and ORTAVANT, 1970) or those with gradual loss in the correlations between testicular measurements and body mass in the adult phase (SOUZA, ARAÚJO, OLIVEIRA et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…while younger anoa more often run away from male anoa. Age factors have a significant effect on animal reproduction performance [28][29][30][31][32][33]. The older the buffalo, the higher the reproductive character and immunity [27], and the greater the chances of successful birth [28].…”
Section: Discussionmentioning
confidence: 99%
“…Male sexual behavior affects the release of LH hormone and anovultaion period in female sheep [29]. The reproductive quality of buffalo is affected by age, weight and size of testes [30]. The reproductive character and immunity of buffalo is higher in males and older than females and younger [31].…”
Section: Introductionmentioning
confidence: 99%